2014
DOI: 10.3389/fonc.2014.00202
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-High Density SNParray in Neuroblastoma Molecular Diagnostics

Abstract: Neuroblastoma serves as a paradigm for applying tumor genomic data for determining patient prognosis and thus for treatment allocation. MYCN status, i.e., amplified vs. non-amplified, was one of the very first biomarkers in oncology to discriminate aggressive from less aggressive or even favorable clinical courses of neuroblastoma. However, MYCN amplification is by far not the only genetic change associated with unfavorable clinical courses. So called “segmental chromosomal aberrations,” (SCAs) i.e., gains or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 62 publications
4
39
0
Order By: Relevance
“…In neuroblastoma, it has been shown that the overall tumor genomic profile determined by copy number analysis of tumor material is of prognostic impact, and genomic copy number profiling using material from tumor cells is considered as a reference for obtaining a tumor genomic profile at the time of diagnosis (11,13,14). We have now undertaken a study of 70 plasma samples obtained at diagnosis to determine the feasibility of using cfDNA isolated from plasma for the study of an overall genomic profile.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In neuroblastoma, it has been shown that the overall tumor genomic profile determined by copy number analysis of tumor material is of prognostic impact, and genomic copy number profiling using material from tumor cells is considered as a reference for obtaining a tumor genomic profile at the time of diagnosis (11,13,14). We have now undertaken a study of 70 plasma samples obtained at diagnosis to determine the feasibility of using cfDNA isolated from plasma for the study of an overall genomic profile.…”
Section: Discussionmentioning
confidence: 99%
“…Current treatment strategies take into account the genomic copy number profile both in patients with low-risk neuroblastoma, as well as in certain patients with high-risk neuroblastoma, aged <18 months (11,12). A genomic copy number profile is routinely assessed on diagnostic tumor tissue, most frequently using pangenomic techniques, such as MLPA, array comparative genomic hybridization (aCGH), or SNPa (11,13,14). However, in some instances, biopsies from a primary or metastatic tumor site are not available, for instance, in severely ill young infants with disseminated disease, whereas in older children biopsies might harbor only a low percentage of tumor cells, thus impacting on molecular genetic analysis.…”
Section: Introductionmentioning
confidence: 99%
“…23,30). CytoScan HD has a genome-wide coverage with more than 2.6 million copy number and SNP markers.…”
Section: Translational Relevancementioning
confidence: 99%
“…Because it includes 750,000 SNP probes, it is possible to detect regions with copy-neutral LOH and low level of mosaicisms. Subclonal frequencies were calculated by evaluating the smooth signal level and the allele difference track pattern and by considering the tumor cell content of the samples as described before (23,30,31).…”
Section: Translational Relevancementioning
confidence: 99%
“…Genome-wide copy number analysis is commonly performed in hypothesis-generating genomics research, including many recent large-scale cancer studies3. It is also growing rapidly in clinical diagnostics as a high-resolution alternative or complement to in situ chromosome analysis45.…”
mentioning
confidence: 99%